2018
DOI: 10.1002/pat.4402
|View full text |Cite
|
Sign up to set email alerts
|

Highly soluble phenylethynyl‐terminated imides derived from mellophanic dianhydride (MPDA)

Abstract: Novel highly soluble phenylethynyl‐endcapped oligoimides with different calculated molecular weights were prepared by using mellophanic dianhydride and bis(4‐amino‐2‐trifluoromethylphenyl)ether in the presence of 4‐phenylethynyl phthalic anhydride as the reactive endcapping agent. The effect of molecular weights of the aromatic oligoimides on their solubility and processability as well as the thermal and mechanical properties of the thermal‐cured polyimides was fully investigated. This kind of phenylethynyl‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Benefiting from its low melt viscosity and better processing window, PMR‐15 composites have been widely used in airplanes, automobiles, and off‐shore oil‐drilling platforms 3,19 . However, the poor thermo‐oxidative and storage stability, harsh curing conditions (600 K, 200–500 psi) as well as the brittleness of cured PIs limited the applications of norbornene (NE) end‐capped prepolymers 14,20 . Due to forming aromatic cross‐linking structure introduced phenylethynyl terminated imide, the thermo‐oxidative stability and toughness of PIs were effectively improved.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from its low melt viscosity and better processing window, PMR‐15 composites have been widely used in airplanes, automobiles, and off‐shore oil‐drilling platforms 3,19 . However, the poor thermo‐oxidative and storage stability, harsh curing conditions (600 K, 200–500 psi) as well as the brittleness of cured PIs limited the applications of norbornene (NE) end‐capped prepolymers 14,20 . Due to forming aromatic cross‐linking structure introduced phenylethynyl terminated imide, the thermo‐oxidative stability and toughness of PIs were effectively improved.…”
Section: Introductionmentioning
confidence: 99%
“…First, the dianhydrides should be asymmetric, because they can decrease the melt viscosity of the oligomers and enhance the T g after cured. That is why asymmetric dianhydrides have been widely investigated lately . Second, there should be flexible segments in molecular chains (like 1,3,4‐APB, 3,4′‐ODA, and 1,4,4‐6FAPB), because they can enhance the processability of the oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, PETIs have received sustained attention over these years. [6][7][8][9][10][11] In recent years, it was found that oligomers with calculated molecular weight of 750 g mol À1 showed good features for resin transfer molding (RTM) processing. RTM is more desirable for composite fabrication than conventional autoclave techniques because of its relatively low manufacturing cost and the solvent-free feature.…”
Section: Introductionmentioning
confidence: 99%